Remote Monitoring of Diabetes: A Cloud-Connected Digital System for Individuals With Diabetes and Their Health Care Providers. (November 2019) - Joubert, Michael; Benhamou, Pierre-Yves; Schaepelynck, Pauline; Hanaire, Hélène; Catargi, Bogdan; Farret, Anne; Fontaine, Pierre; Guerci, Bruno; Reznik, Yves; Jeandidier, Nathalie; Penfornis, Alfred; Borot, Sophie; et al.
Benefits of telemedicine have been proven in the field of diabetes. Among a number of technical solutions, Diabeo® has been studied in both type 1 and type 2 diabetes with intensive insulin therapy. This digital therapeutic system contains a self-monitoring glucose logbook and offers automated insulin dose recommendations thanks to a fully customizable algorithm. In addition, the cloud-based dedicated software also has features to facilitate remote monitoring, including a platform for diabetes nurses who perform coaching and treatment adjustment. A detailed description of this telemedicine system is provided, as well as results of completed clinical studies. In particular, TeleDiab 1's positive results on HbA1c in type 1 diabetes are detailed. We conclude with a discussion of the role of this telemedicine system within the landscape of mobile apps for diabetes.